Time‐traveling seeds reveal that plant regeneration and growth traits are responding to climate change - Susan E. Everingham; Catherine A. Offord; Manon E. B. Sabot; Angela T. Moles (Ecology, 2021)
Studies assessing the biological impacts of climate change typically rely on long‐term, historic data to measure trait responses to climate through time. Here, we overcame the problem of absent historical data by using resurrected seeds to capture historic plant‐trait data for a number of plant regeneration and growth traits. We collected seed and seedling trait measurements from resurrected historic seeds and compared these with modern seed and seedling traits collected from the same species in the same geographic location. We found a total of 43 species from southeastern Australia for which modern/historic seed pairs could be located. These species were located in a range of regions that have undergone different amounts of climate change across a range of temperature, precipitation, and extreme measures of climate. There was a correlation between the amount of change in climate metrics, and the amount of change in plant traits. Using stepwise model selection, we found that for all regeneration and growth trait changes (except change in stem density), the most accurate model selected at least two measures of climate change. Changes in extreme measures of climate, such as heat‐wave duration and changes in climate variability, were more strongly related to changes in regeneration and growth traits than changes in mean climate metrics. Across our species, for every 5% increase in temperature variability, there was a threefold increase in the probability of seed viability and seed germination success. An increase of 1 d in the maximum duration of dry spells through time led to a 1.5‐fold decrease in seed viability and seeds became 30% flatter/thinner. Regions where the maximum heat‐wave duration had increased by 10 d saw a 1.35‐cm decrease in seedling height and a 1.04‐g decrease in seedling biomass. Rapid responses in plant traits to changes in climate may be possible; however, it is not clear whether these changes will be fast enough for plants to keep pace with future climate change.